Base free N-alkylation of anilines with ArCH2OH and transfer hydrogenation of aldehydes/ketones catalyzed by the complexes of η5-Cp*Ir(iii) with chalcogenated Schiff bases of anthracene-9-carbaldehyde. Issue 11 (15th February 2018) - Dubey, Pooja; Gupta, Sonu; Singh, Ajai K.
Abstract : Base free transfer hydrogenation and N -alkylation of aniline with benzyl alcohol were catalyzed by Ir(iii ) complexes (0.1–0.5 mol%). Abstract : The condensation of anthracene-9-carbaldehyde with 2-(phenylthio/seleno)ethylamine results in Schiff bases [PhS(CH2 )2 CN-9-C14 H9 ](L1 ) and [PhSe(CH2 )2 CN-9-C14 H9 ] (L2 ). On their reaction with [(η 5 -Cp*)IrCl(μ-Cl)]2 and CH3 COONa at 50 °C followed by treatment with NH4 PF6, iridacycles, [(η 5 -Cp*)Ir(L-H )][PF6 ] (1 :L =L1 ;2 :L =L2 ), result. The same reaction in the absence of CH3 COONa gives complexes [(η 5 -Cp*)Ir(L )Cl][PF6 ] (3–4 ) in whichL =L1 (3 )/L2 (4 ) ligates in a bidentate mode. The ligands and complexes were authenticated with HR-MS and NMR spectra [ 1 H, 13 C{ 1 H} and 77 Se{ 1 H} (in the case ofL2 and its complexes only)]. Single crystal structures ofL2 and half sandwich complexes1–4 were established with X-ray crystallography. Three coordination sites of Ir in each complex are covered with η 5 -Cp* and on the remaining three, donor atoms present are: N, S/Se and C − /Cl −, resulting in a piano-stool structure. The moisture and air insensitive1–4 act as efficient catalysts under mild conditions for base free N -alkylation of amines with benzyl alcohols and transfer hydrogenation (TH) of aldehydes/ketones. The optimum loading of1–4 as a catalyst is 0.1–0.5 mol% for both the activations. The best reaction temperature is 80 °C for transfer hydrogenation and 100 °C for N -alkylation. The mercury poisoning test supports a homogeneous pathway for both the reactions catalyzed by1–4 . The two catalytic processes are most efficient with3 followed by4 >1 >2 . The mechanism proposed on the basis of HR-MS of the reaction mixtures of the two catalytic processes taken after 1–2 h involves the formation of an alkoxy and hydrido species. The real catalytic species proposed in the case of iridacycles results due to the loss of the Cp* ring.